The Development of Critical Thinking Ability and Teamwork and Collaboration Competence using the Problem–based Learning with the Simulation Based Learning for Grade 9 Students - Lerdkhampom , Thitiwat; Duangwilai, Dhanita (Dhammathas Academic Journal, 2024)
These objectives of this research were 1) to develop the critical thinking ability of grade 9 students through problem-based learning and the simulation based learning to enable 80% of students to pass 75% or more of the criteria, and 2) to develop the teamwork and collaboration competence of grade 9 students through problem-based learning and the simulation based learning to enable 80% of students to pass 75% or more of the criteria. The target group comprised 40 students grade 9 at Nongbuadaengwittaya School studying in the second semester of the 2023 academic year. The study included action research comprising 3 cycles. The research tools can be divided into 3 types including. 1) action research tools involving action-level learning plans that emphasize critical thinking ability and teamwork and collaboration competence, with problem-based learning and the simulation based learning. 2) the tools used to reflect on the operational results, consisting of the assessment of student performance in critical thinking ability. Final test also used to measure critical thinking ability. After completed ; by using student teamwork competency assessment form, learning management record form, teacher behavior observation form, student behavior observation form and student interview form. 3) tools to assess the development of critical thinking ability and teamwork and collaboration competence. Quantitative data were analyzed using basic statistics, namely mean ( ) standard deviation (S.D.) and percentage. Data were analyzed by content analysis and summarized in the essay with the analytical description. The research results found that: 1. Students have the development of critical thinking ability, accounting for 80.92 percent, which pass the criteria. Accounted for 82.50 percent, according to the specified criteria. 2. Students have the development of teamwork and collaboration competence, accounting for 79.15 percent, which pass the criteria. Accounted for 85.00 percent, according to the specified criteria.